PERLINDUNGAN DATA PRIBADI KONSUMEN PADA TRANSAKSI PAYLATER - Fadhli, Zawil; Rahayu, Sri Walny; Gani, Iskandar A (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
Abstract Article 26 paragraph (1) of the Law of the Republic of Indonesia Number 19 of 2016 on Amendments to Law Number 11 of 2008 on Information and Electronic Transactions (Law No.19/2016) has mentioned that any use of a person's personal data, must be done on the basis of the consent of the owner of personal data. In Financial Technology with paylater payment scheme that conducts borrowing activities by utilizing consumer personal data to transact in the form of Population Master Number as the main condition. The formulation of the issues studied is an aspect of the position of electronic system organizers as paylater providers in the protection of consumer personal data as well as arrangements on the guarantee of personal data protection according to the Law No.19/2016 and The Minister of Communication and Information Regulation No. 20 of 2016 on The Protection of Personal Data in Electronic Systems (Permenkominfo No.20/2016). Research methods use normative juridical through literature studies by studying and reviewing other legal materials sourced from primary and secondary legal materials. The results showed that there is no legal certainty regarding the position of Paylater providers in order to protect consumers' personal data, Article 19 paragraph (4) of Financial Services Authority Regulation No. 77/ POJK.01/2016 on Information Technology-Based Lending Services (POJK No. 77/POJK.01/2016) mentioned that consumer personal data is not included as access to information provided to lenders. In addition, the regulations governing personal data only contain the general understanding of personal data and have not accommodated concrete forms of protected personal data objects so that the Population Master Number and Sensitive Data have no legal basis as objects of consumer personal data. Therefore, more comprehensive legislation is needed that can regulate the position of paylater providers in protecting consumer personal data and concretely regulating the forms of consumer personal data objects as a form of legal certainty over privacy rights. Keywords: consumer protection; data privacy; paylater Abstrak Pasal 26 ayat (1) Undang-Undang Republik Indonesia Nomor 19 Tahun 2016 tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik (UU No. 19/2016) telah disebutkan bahwa setiap penggunaan data pribadi seseorang, harus dilakukan atas dasar persetujuan dari pemilik data pribadi. Pada Financial Technology dengan skema pembayaran paylater yang melakukan kegiatan pinjam-meminjam dengan memanfaatkan data pribadi konsumen untuk bertransaksi dalam bentuk Nomor Induk Kependudukan sebagai syarat utama. Rumusan masalah yang dikaji adalah aspek kedudukan penyelenggara sistem elektronik sebagai penyedia paylater dalam perlindungan data pribadi konsumen serta pengaturan tentang jaminan perlindungan data pribadi menurut UU No. 19/2016 dan Peraturan Menteri Kominfo Nomor 20 Tahun 2016 tentang Perlindungan Data Pribadi Dalam Sistem Elektronik (Permenkominfo No. 20/2016). Metode penelitian menggunakan yuridis normatif melalui studi kepustakaan dengan menelaah dan mengkaji materi bahan hukum lainnya yang bersumber dari bahan hukum primer dan sekunder. Hasil penelitian menunjukkan bahwa belum adanya kepastian hukum terkait kedudukan penyedia paylater dalam rangka melindungi data pribadi konsumen, Pasal 19 ayat (4) Peraturan Otoritas Jasa Keuangan Nomor 77/POJK.01/2016 tentang Layanan Pinjam Meminjam Uang Berbasis Teknologi Informasi (POJK No. 77/POJK.01/2016) disebutkan bahwa data pribadi konsumen tidak termasuk sebagai akses informasi yang diberikan kepada pemberi pinjaman. Selain itu, peraturan yang mengatur tentang data pribadi hanya memuat pengertian data pribadi secara umum dan belum mengakomodasikan bentuk-bentuk konkrit dari objek data pribadi yang dilindungi sehingga Nomor Induk Kependudukan serta Data Sensitif tidak memiliki dasar hukum sebagai objek data pribadi konsumen. Oleh karena itu, diperlukan Undang-undang yang lebih komprehensif yang dapat mengatur kedudukan pihak penyediapaylater dalam melindungi data pribadi konsumen serta mengatur dengan konkrit bentuk-bentuk dari objek data pribadi konsumen sebagai wujud dari kepastian hukum atas hak privasi. Kata kunci: data pribadi; paylater; perlindungan konsumen